Factors affecting customer retention among water equipment and services companies in Kenya - Kahiga, M. (Strathmore University, 2025)
Retaining customers is one of the key growth strategies for long-term business growth. The main objective of this study was to establish the factors that influence customer retention in the water equipment and services industry in Kenya. The specific objectives were to determine the effects of customer engagement, product quality, pricing and product diversification on customer retention in the water equipment and services industry in Kenya. The study was underpinned by the commitment-trust theory of relationship marketing and the conversion model. Positivism philosophy was used to guide the research methodology. The descriptive cross-sectional research design was adopted for the proposed study. Judgmental sampling strategy was employed to access respondents from a population consisting of 65 water equipment and services companies. The sample consisted of 97 respondents from these companies consisting of sales and marketing managers. Data collection was performed by distributing structured questionnaires. The collected data was analyzed using the Statistical Package for Social Sciences (SPSS) version 26. The results indicated that customer engagement had a significant positive effect on customer retention; thus, improving customer engagement can increase customer retention. Additionally, the findings showed that product quality had a significant positive effect on customer retention, which means improving product quality can improve customer retention in the water equipment and services sector. Moreover, the results showed that price did not have a significant effect on customer retention. Therefore, pricing strategies are not linked to customer retention in the water equipment and services sector. Lastly, the findings from this study revealed that product diversification had a significant positive effect on customer retention. Consequently, product diversification is a potentially effective strategy that water equipment and services company can use to improve customer retention. From the findings, this study recommends that policymakers should adopt standards for product quality in the water equipment and services sector. Additionally, this study recommends that managers should adopt practices to improve customer engagement and product diversification strategies. Some recommended strategies that managers can use to improve customer engagement include customer feedback, knowledgeable sales representatives, reachability of the company, professionalism of customer support and providing training to customers, which are based on the indicators used in this research. Additionally, some strategies that managers can utilize to implement product diversification include providing variety in options, quality and pricing.
Full - text thesis